Cooperation and counterparts in WHO actions: notes on global health geopolytics - Darsie, Camilo; Weber, Douglas; de Faria, Mateus Aparecido; Rocha, Cristianne Maria Famer (Geografares, 2018)
This essay aims, from official documents and specialized literature, to analyze the performance of WHO since its origin and its role in matters related to global health, highlighting the dynamics of cooperation-counterpart. This dynamic is a result of the complexification of international relations, involving member States, non-state actors and development agencies, in order not only to follow WHO guidelines but also to encourage them to prioritize certain global health projects.
Keywords: Global Healt; International Cooperation; Public Health; WHO